Intensification of microalgae drying and oil extraction process by vapor recompression and heat integration. (May 2016) - Song, Chunfeng; Liu, Qingling; Ji, Na; Deng, Shuai; Zhao, Jun; Kitamura, Yutaka
Graphical abstract: Highlights: Microalgae drying and oil extraction process was intensified. Condensation heat was reused by vapor recompression and heat integration. Energy requirement was reduced by 52.4% compared to the conventional route. Operational cost decreased by 81.0% compared to the conventional route. Abstract: Reducing energy penalty caused by drying and oil extraction is the most critical challenge in microalgae biodiesel production. In this study, vapor recompression and heat integration are utilized to optimize the performance of wet microalgae drying and oil extraction. In the microalgae drying stage, the hot exhaust stream is recompressed and coupled with wet microalgae to recover the condensate heat. In the oil extraction stage, the exergy rate of recovered solvent is also elevated by compressor and then exchanged heat with feed and bottom stream in the distillation column. Energy and mass balance of the intensified process is investigated and compared with the conventional microalgae drying-extraction process. The simulation results indicated that the total energy consumption of the intensified process can be saved by 52.4% of the conventional route.